KONSEP IJMAK MENURUT FAZLUR RAHMAN: Studi Kritis terhadap Teori Ijmak Imam Asy-Syafi'i - Chairul Fahmi (Sharia and Law Faculty, 2017)
The aim of this research is to find out the concept of ijmak (consensus) based on Fazlur Rahman’s thought. As a general rule, ijmak is understood as a source of Islamic law after Alquran and hadis. Therefore, ijmak has been designed as a concrete concept and its position is imposible to be wrong. Moreover, it’s not available for difference of opinions among Mujtahids during the process of ijmak. Meanwhile, Fazlur Rahman believes that ijmak as a democracy process which could be every Muslim scholar (mujtahids) to have difference of opinions. This study based on library research by exploring and examining the books related to Fazlur Rahman’s thought. The result of this study stated that ijmak as a process of opinion interaction among mujtahid to each other and will be legalized through the formal institution (council/legislative).